Chapter Biographies (Taylor & Francis, 2023)
The Hispanic and Anglo worlds are often portrayed as the Cain and Abel of Western culture, antagonistic and alien to each other. This book challenges such view with a new critical conceptual framework – the ‘Hispanic-Anglosphere’ – to open a window into the often surprising interactions of individuals, transnational networks and global communities that, it argues, made of the British Isles (England, Ireland, Scotland, Wales, the Channel Islands and the Isle of Man) a crucial hub for the global Hispanic world, a launching-pad and a bridge between Spanish Europe, Africa, America and Asia in the late eighteenth to the early twentieth centuries. Perhaps not unlike today, that was a time marked by social uncertainty, pandemics, the dislocation of global polities and the rise of radicalisms. The volume offers insights on many themes including trade, the arts, education, language, politics, the press, religion, biodiversity, philanthropy, anti-slavery and imperialism. Established academics and rising stars from different continents and disciplines combined original, primary research with a wide range of secondary sources to produce a rich collection of ten case-studies, 25 biographies and seven samples of interpreted material culture, all presented in an accessible style appealing to scholars, students and the general reader alike.